Analisis Pengaruh Human Relation, Komunikasi antar Karyawan dan Lingkungan Kerja terhadap Kinerja Karyawan Toko Salman - Maulana, Muhamad Fikri; Dewi, Anita Sumelvia; Syahputra, Erwin (Jurnal Bisnis Islam dan Kewirausahaan, 2023)
This research only focuses on examining the influence of Human Relations, communication between employees and the work environment on employee performance at the SALMAN SHOP which is located in the Pondok Pesantren area, Jl. Raya Ploso Ploso Hamlet, Ploso Village, Mojo District, Kediri Regency. In this research sampling technique, researchers used a saturated sampling method. The questionnaire was used as the main data collector with multiple linear regression as analysis. The results of calculations using SPSS show that there is a positive and significant influence between the Human Relations variable on employee performance. However, employee communication and work environment variables do not have a significant effect on employee performance. For this reason, Salman's shop must pay attention to the human relations of its employees so that performance is maintained